The letters of the Rožmberk sisters : noblewomen in fifteenth-century Bohemia : translated from Czech and German with introduction, notes and interpretive essay - Rožmberka, Perchta z, active 15th century (Library of medieval women., 2001)
The letters of Perchta and Anezka offer an illuminating insight into how two aristocractic women in fifteenth-century Bohemia saw themselves and their lives. The central topic is Perchta's deep unhappiness at her father's choice of husband for her. This rare discussion of a situation that must have faced many women in the middle ages is valuable for its illustration of how much a woman might do to influence plans made for her, made all the more interesting by the vigorous personalities of the two sisters and the incidental illumination of family and castle life.